Ultra-high performance concrete prepared from continuously-graded basalt sand and preparation method of ultra-high performance concrete

By using continuous graded basal sand and modified blends to prepare ultra-high performance concrete, the problem of insufficient performance of traditional quartz sand concrete is solved, and high strength, high toughness, wear resistance, light weight and good asphalt adhesion is achieved. comprehensive performance and improve durability.

CN119462001APending Publication Date: 2025-02-18XIAMEN TIANRUN JINLONG BUILDING MATERIAL
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411461410.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Traditional ultra-high performance concrete uses quartz sand as fine aggregate, which has the potential hazards of strong water absorption, high brittleness, easy to form microcracks, alkali-silicic acid reactions, and it is difficult to have high strength, high toughness, wear resistance, light weight and Good asphalt adhesion and other properties.

Method used

Continuous graded black sand is used as fine aggregate, combined with modified blends to replace part of cement, and ultra-high performance concrete is prepared. The particle size of black sand is divided into three categories, and the dispersion and reactivity of the blend are improved through surface modification treatment.

Benefits of technology

It realizes that ultra-high performance concrete has high strength and high toughness properties, and has good wear resistance, light weight, and good adhesion to asphalt. It overcomes the possible alkali-silicic acid of traditional quartz sand concrete. Respond to hazards and improves durability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of concrete, in particular to ultra-high performance concrete prepared from continuously-graded basalt sand and a preparation method of the ultra-high performance concrete. The ultra-high performance concrete is prepared from the following raw material components: cement, silica fume, a modified admixture, basalt sand, steel fibers, a viscosity reducer, a water-retaining agent, a defoaming agent, a water reducing agent and water, the basaltic sand comprises a first kind of basaltic sand, a second kind of basaltic sand and a third kind of basaltic sand; the modified admixture is obtained by carrying out surface modification treatment on a mixture through a surface modifier solution; the mixture is prepared by mixing mineral powder, fly ash, ceramic polishing powder and diethanolisopropanolamine and carrying out ball milling treatment. Under the condition that the ultra-high performance concrete has good working performance, the advantages of high strength and high toughness of the ultra-high performance concrete can be brought into full play, and the ultra-high performance concrete has the pavement performance of good wear resistance, light weight, good adhesion with asphalt and the like, and also has the advantage of good durability. In addition, the modified admixture is used for replacing part of cement, so that the total material cost is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of concrete technology, and in particular to an ultra-high performance concrete prepared with continuously graded basalt sand and a preparation method thereof. Background Art

[0002] Innovation, low carbon, green environmental protection and sustainability are the main themes of the development of the times, and are also the big stage for advanced cement-based materials UHPC to play a role.

[0003] Ultra-high performance concrete (UHPC) is a special type of concrete with extremely high strength and durability. Through special mix design and manufacturing process, it can achieve performance indicators far higher than traditional concrete. The main features of UHPC include high strength, high toughness and low permeability, and it is widely used in bridge construction, high-rise buildings and protective engineering.

[0004] Traditional ultra-high performance concrete mostly uses quartz sand as fine aggregate, but quartz sand has strong water absorption, which may cause the concrete to be highly cohesive and difficult to disperse. Quartz sand is also very brittle, which may lead to the formation of microcracks inside the concrete, thereby affecting the durability of the structure. Quartz sand may react with the alkaline components in the concrete, resulting in an alkali-silica reaction, which is a potential hazard that can cause the concrete to expand and eventually crack.

[0005] In addition, concrete with good wear resistance, light weight, and good adhesion to asphalt is widely welcomed in the market due to its good road performance. However, the existing traditional ultra-high performance concrete using quartz sand as fine aggregate is generally difficult to combine light weight and good adhesion to asphalt while maintaining high strength and high toughness.

[0006] Therefore, it is necessary to find a method for preparing ultra-high performance concrete with good fine aggregate to replace quartz sand, which can not only give full play to the advantages of high strength and high toughness of ultra-high performance concrete, but also have road performance such as good wear resistance, light weight, and good adhesion to asphalt, and it can overcome the potential hazard of concrete cracking caused by alkali-silica reaction in traditional concrete using quartz sand fine aggregate. Summary of the invention

[0007] In order to solve the problems mentioned in the above background technology, the present application provides an ultra-high performance concrete prepared with continuously graded basalt sand. The ultra-high performance concrete can give full play to the advantages of high strength and high toughness of ultra-high performance concrete while having good working performance, and can also have road performance such as good wear resistance, light weight, and good adhesion to asphalt. At the same time, it also has the advantage of good durability.

[0008] The ultra-high performance concrete prepared with continuously graded basalt sand provided in the present application comprises the following raw material components: cement, silica fume, modified admixture, basalt sand, steel fiber, viscosity reducer, water retaining agent, defoamer, water reducing agent and water; wherein the basalt sand comprises first-class basalt sand, second-class basalt sand and third-class basalt sand, the particle sizes of the first-class basalt sand, the second-class basalt sand and the third-class basalt sand are (0.2-0.4) mm, (0.4-0.8) mm and (0.8-1.0) mm respectively, and the mass ratio of the first-class basalt sand, the second-class basalt sand and the third-class basalt sand is (1-4): (6-8): (2-4); the modified admixture is obtained by surface-modifying the mixture with a surface modifier solution; wherein the mixture is obtained by mixing and ball-milling mineral powder, fly ash, ceramic polishing powder and diethanol monoisopropanolamine.

[0009] In some embodiments, the preparation process of the modified admixture is as follows: mineral powder, fly ash, and ceramic polishing powder are mixed to form a mixed powder, and then diethanol monoisopropanolamine is added for ball milling for 40 to 60 minutes to obtain a mixture; then a surface modifier solution is added for surface modification, and the mixture is stirred at 40 to 80°C for (5 to 10) minutes, filtered, and finally dried to obtain the modified admixture; wherein the mass ratio of the mineral powder, the fly ash, and the ceramic polishing powder is (1 to 3): (3 to 5): (2 to 6); the amount of diethanol monoisopropanolamine is 0.01% to 0.03% of the mass of the mixed powder; and the amount of the surface modifier solution is 8 to 12 times the mass of the mixture.

[0010] In some embodiments, the basalt sand is obtained by crushing and screening basalt; the basalt sand consists of first type basalt sand, second type basalt sand and third type basalt sand.

[0011] In some embodiments, it includes the following raw material components, measured by mass: 480-800 parts of cement, 100-200 parts of silica fume, 330-650 parts of modified admixture, 1000-1500 parts of basalt sand, 40-160 parts of steel fiber, 2-10 parts of viscosity reducer, 5-10 parts of water retaining agent, 2-6 parts of defoaming agent, 1-3 parts of water reducing agent, and 192-250 parts of water.

[0012] In some embodiments, it includes the following raw material components, measured by mass: 600-700 parts of silicate cement, 120-180 parts of silica fume, 400-600 parts of modified admixtures, 1200-1400 parts of basalt sand, 60-120 parts of steel fibers, 4-8 parts of viscosity reducers, 6-8 parts of water retaining agents, 2-4 parts of defoaming agents, 1-2 parts of water reducing agents, and 206-240 parts of water.

[0013] In some embodiments, the cement is one or a combination of P·I 52.5R silicate cement, P·II 52.5R silicate cement, and P·O 52.5R ordinary silicate cement; the silica fume is one or a combination of white silica fume, semi-densified silica fume, and fully-densified silica fume, and its bulk density is 500 kg / m 3 .

[0014] In some embodiments, the steel fiber is a copper-plated steel fiber with a length of 9 to 17 mm, a diameter of 0.1 to 0.3 mm, and a tensile strength of >2100 MPa.

[0015] In some embodiments, the water reducing agent has a water reducing rate of 30-36%; the water retaining agent is a copolymer of sodium polyacrylate and polyacrylamide, with a viscosity of 200s and a sodium polyacrylate content of 88%.

[0016] The present application also provides a method for preparing ultra-high performance concrete prepared using continuously graded basalt sand as described above, which comprises the following preparation steps: According to the mass ratio, cement, silica fume, modified admixture and basalt sand are first mixed to obtain mixture A, and mixture A is stirred and mixed evenly; a certain amount of water is added to the mixture A by spraying, and the mixture is stirred to obtain mixture B; a certain amount of viscosity reducer, water retention agent, defoamer and water reducing agent are added to the mixture B, and the mixture is stirred and mixed to obtain mixture C; steel fibers are evenly sprinkled into the mixture C through a sieve, and the ultra-high performance concrete is obtained after stirring evenly.

[0017] In some embodiments, mixture A is placed in a mortar mixer and stirred for 1 to 3 minutes; a certain amount of water is added to mixture A by spraying, and stirred for 3 to 6 minutes to obtain mixture B; a certain amount of viscosity reducer, water retaining agent, defoamer and water reducing agent is added to mixture B, and stirred for 2 to 4 minutes to obtain mixture C; steel fibers are evenly sprinkled into mixture C through a sieve, and stirred for 2 to 3 minutes to obtain the ultra-high performance concrete.

[0018] Compared with the existing technology, this application has the following technical effects: The present application provides an ultra-high performance concrete prepared with continuously graded basalt sand, which can give full play to the advantages of high strength and high toughness of ultra-high performance concrete while having good working performance, and can also have road performance such as good wear resistance, light weight, good adhesion to asphalt, and good durability. In addition, the ultra-high performance concrete solution uses modified admixtures to replace part of the cement, reducing the overall material cost. DETAILED DESCRIPTION

[0019] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application will be described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0020] The present application provides an operation example of a method for preparing ultra-high performance concrete using continuously graded basalt sand as follows: (1) According to the mass ratio of the formula, cement, silica fume, modified admixture and basalt sand are first mixed to obtain mixture A, and then mixture A is placed in a mortar mixer and stirred for 1 to 3 minutes; (2) Then, a certain amount of water is added to the mixture A by spraying, and the mixture is stirred for 3 to 6 minutes to obtain a mixture B; (3) Add a certain amount of viscosity reducer, water retaining agent, defoamer and water reducing agent to mixture B and stir for 2 to 4 minutes to obtain mixture C; (4) The steel fibers are evenly sprinkled into the mixture C through a sieve and stirred for 2 to 3 minutes to obtain the ultra-high performance concrete.

[0021] Among them, the specific concrete formula is: Calculated by mass, it includes the following raw material components: 480-800 parts of cement, 100-200 parts of silica fume, 330-650 parts of modified admixture, 1000-1500 parts of basalt sand, 40-160 parts of steel fiber, 2-10 parts of viscosity reducer, 5-10 parts of water retaining agent, 2-6 parts of defoaming agent, 1-3 parts of water reducing agent and 192-250 parts of water.

[0022] Preferably, it includes the following raw material components, measured by mass: 600-700 parts of silicate cement, 120-180 parts of silica fume, 400-600 parts of modified admixtures, 1200-1400 parts of basalt sand, 60-120 parts of steel fibers, 4-8 parts of viscosity reducers, 6-8 parts of water retaining agents, 2-4 parts of defoaming agents, 1-2 parts of water reducing agents, and 206-240 parts of water.

[0023] More preferably, it includes the following raw material components, measured by mass: 650 parts of cement, 150 parts of silica fume, 490 parts of modified admixture, 1300 parts of basalt sand, 90 parts of steel fiber, 6 parts of viscosity reducer, 7 parts of water retaining agent, 3 parts of defoaming agent, 1.5 parts of water reducing agent, and 228 parts of water.

[0024] The preparation process of the modified admixture is as follows: ore powder, fly ash and ceramic polishing powder are mixed to form a mixed powder, and then diethanol monoisopropanolamine is added to perform ball milling for 40 to 60 minutes to obtain a mixture; then a surface modifier solution is added to perform surface modification treatment, and the mixture is stirred at 40 to 80° C. for (5 to 10) minutes, filtered, and finally dried to obtain the modified admixture; Among them, the mass ratio of the mineral powder, fly ash and ceramic polishing powder is (1-3): (3-5): (2-6); the amount of diethanol monoisopropanolamine is 0.01% to 0.03% of the mass of the mixed powder; and the amount of the surface modifier solution is 8 to 12 times the mass of the mixture.

[0025] The basalt sand is obtained by crushing and screening basalt, and specifically consists of first-class basalt sand, second-class basalt sand and third-class basalt sand. The particle sizes of the first-class basalt sand, the second-class basalt sand and the third-class basalt sand are (0.2-0.4) mm, (0.4-0.8) mm and (0.8-1.0) mm respectively, and the mass ratio of the first-class basalt sand, the second-class basalt sand and the third-class basalt sand is (1-4): (6-8): (2-4).

[0026] The present invention also provides embodiments and comparative examples as shown in Table 1: Example 1 formula: Calculated by mass, it includes the following raw material components: 800 parts of cement, 150 parts of silica fume, 330 parts of modified admixtures, 1024 parts of basalt sand, 40 parts of steel fiber, 2 parts of viscosity reducer, 5 parts of water retaining agent, 2 parts of defoaming agent, 1 part of water reducing agent, and 206 parts of water.

[0027] The modified admixture is formed by mixing mineral powder, fly ash and ceramic polishing powder in a mass ratio of 1:3:2, then adding 0.02% of the mass of the mixed powder diethanol monoisopropanolamine for ball milling for 40 minutes to obtain a mixture, then adding a surface modifier solution with a mass of 10 times that of the mixture for surface modification, stirring at 60°C for 60 minutes, filtering with a filter, and finally drying in an oven to obtain a modified admixture. Among them, the surface modifier solution used is an aluminate coupling agent solution.

[0028] Among them, basalt sand is screened after crushing basalt, and is composed of first-class basalt sand, second-class basalt sand and third-class basalt sand. The particle sizes of the first-class basalt sand, the second-class basalt sand and the third-class basalt sand are 0.2-0.4mm, 0.4-0.8mm and 0.8-1.0mm respectively, and they are mixed in a mass ratio of 1:3:1.

[0029] The cement is P·Ⅱ52.5R silicate cement, and the silica fume is selected from semi-densified silica fume with a bulk density of 500kg / m 3The steel fiber used is copper-plated steel fiber, with a length of 9.2 mm, a diameter of 0.2 mm, and a tensile strength of >2100 MPa. The water-reducing agent used has a water-reducing efficiency of 35%. The water-retaining agent used is a copolymer of sodium polyacrylate and polyacrylamide, with a viscosity of 200s and a sodium polyacrylate content of 88%; the defoaming agent used is a polyether-modified silicone defoaming agent.

[0030] The preparation process of ultra-high performance concrete includes the following steps: (1) According to the mass ratio of the formula, cement, silica fume, modified admixture and basalt sand are first mixed to obtain mixture A, and then mixture A is placed in a mortar mixer and stirred for 1 min; (2) Then, a certain amount of water was added to the mixture A by spraying and stirred for 4 minutes to obtain a mixture B; (3) Add a certain amount of viscosity reducer, water retaining agent, defoamer and water reducing agent to mixture B, stir and mix for 3 minutes to obtain mixture C; (4) The steel fibers are evenly sprinkled into the mixture C through a sieve and stirred for 2 minutes to obtain the ultra-high performance concrete.

[0031] Example 2 formula: Calculated by mass, it includes the following raw material components: 694 parts of cement, 150 parts of silica fume, 436 parts of modified admixtures, 1024 parts of basalt sand, 40 parts of steel fiber, 2 parts of viscosity reducer, 5 parts of water retaining agent, 2 parts of defoaming agent, 1 part of water reducing agent, and 206 parts of water.

[0032] The modified admixture is prepared by mixing mineral powder, fly ash and ceramic polishing powder in a mass ratio of 1:3:2 to form a mixed powder, then adding 0.02% of the mass of the mixed powder diethanol monoisopropanolamine for ball milling for 40 minutes to obtain a mixed material, and then adding a surface modifier solution with a mass of 10 times that of the mixed material for surface modification treatment, stirring at 60°C for 60 minutes, filtering with a filter, and finally drying in an oven to obtain a modified admixture. Wherein, the surface modifier solution used is an aluminate coupling agent solution.

[0033] Basalt sand is obtained by crushing and screening basalt, and is composed of first-class basalt sand, second-class basalt sand and third-class basalt sand. The particle sizes of the first-class basalt sand, the second-class basalt sand and the third-class basalt sand are 0.2-0.4mm, 0.4-0.8mm and 0.8-1.0mm respectively, and they are mixed in a mass ratio of 1:3:1.

[0034] The cement is P·Ⅱ52.5R silicate cement; wherein the silica fume is selected from semi-densified silica fume with a bulk density of 500kg / m 3The steel fiber used is copper-plated steel fiber, with a length of 9.2 mm, a diameter of 0.2 mm, and a tensile strength of >2100 MPa. The water-reducing agent used has a water-reducing efficiency of 35%. The water-retaining agent used is a copolymer of sodium polyacrylate and polyacrylamide, with a viscosity of 200s and a sodium polyacrylate content of 88%. The defoaming agent used is a polyether-modified silicone defoaming agent.

[0035] The preparation process of ultra-high performance concrete includes the following steps: (1) According to the mass ratio of the formula, cement, silica fume, modified admixture and basalt sand are first mixed to obtain mixture A, and then mixture A is placed in a mortar mixer and stirred for 1 min; (2) Then, a certain amount of water was added to the mixture A by spraying and stirred for 4 minutes to obtain a mixture B; (3) Add a certain amount of viscosity reducer, water retaining agent, defoamer and water reducing agent to mixture B, stir and mix for 3 minutes to obtain mixture C; (4) The steel fibers are evenly sprinkled into the mixture C through a sieve and stirred for 2 minutes to obtain the ultra-high performance concrete.

[0036] Example 3 formula: Calculated by mass, it includes the following raw material components: 587 parts of cement, 150 parts of silica fume, 543 parts of modified admixtures, 1024 parts of basalt sand, 40 parts of steel fiber, 2 parts of viscosity reducer, 5 parts of water retaining agent, 2 parts of defoaming agent, 1 part of water reducing agent, and 206 parts of water.

[0037] The modified admixture is formed by mixing mineral powder, fly ash and ceramic polishing powder in a mass ratio of 1:3:2, then adding 0.02% of the mass of the mixed powder diethanol monoisopropanolamine for ball milling for 40 minutes to obtain a mixture, then adding a surface modifier solution with a mass of 10 times that of the mixture for surface modification, stirring at 60°C for 60 minutes, filtering with a filter, and finally drying in an oven to obtain a modified admixture. Among them, the surface modifier solution used is an aluminate coupling agent solution.

[0038] Among them, basalt sand is screened after crushing basalt, and is composed of first-class basalt sand, second-class basalt sand and third-class basalt sand. The particle sizes of the first-class basalt sand, the second-class basalt sand and the third-class basalt sand are 0.2-0.4mm, 0.4-0.8mm and 0.8-1.0mm respectively, and they are mixed in a mass ratio of 1:3:1.

[0039] The cement is P·Ⅱ52.5R silicate cement; the silica fume is selected from semi-densified silica fume with a bulk density of 500kg / m 3The steel fiber used is copper-plated steel fiber, with a length of 9.2 mm, a diameter of 0.2 mm, and a tensile strength of >2100 MPa. The water-reducing agent used has a water-reducing efficiency of 35%. The water-retaining agent used is a copolymer of sodium polyacrylate and polyacrylamide, with a viscosity of 200s and a sodium polyacrylate content of 88%; the defoaming agent used is a polyether-modified silicone defoaming agent.

[0040] The preparation process of ultra-high performance concrete includes the following steps: (1) According to the mass ratio of the formula, cement, silica fume, modified admixture and basalt sand are first mixed to obtain mixture A, and then mixture A is placed in a mortar mixer and stirred for 1 min; (2) Then, a certain amount of water was added to the mixture A by spraying and stirred for 4 minutes to obtain a mixture B; (3) Add a certain amount of viscosity reducer, water retaining agent, defoamer and water reducing agent to mixture B, stir and mix for 3 minutes to obtain mixture C; (4) The steel fibers are evenly sprinkled into the mixture C through a sieve and stirred for 2 minutes to obtain the ultra-high performance concrete.

[0041] Example 4 raw material: Calculated by mass, it includes the following raw material components: 480 parts of cement, 150 parts of silica fume, 650 parts of modified admixtures, 1024 parts of basalt sand, 40 parts of steel fiber, 2 parts of viscosity reducer, 5 parts of water retaining agent, 2 parts of defoaming agent, 1 part of water reducing agent, and 206 parts of water.

[0042] The modified admixture is formed by mixing mineral powder, fly ash and ceramic polishing powder in a mass ratio of 1:3:2, then adding 0.02% of the mass of the mixed powder diethanol monoisopropanolamine for ball milling for 40 minutes to obtain a mixture, then adding a surface modifier solution with a mass of 10 times that of the mixture for surface modification, stirring at 60°C for 60 minutes, filtering with a filter, and finally drying in an oven to obtain a modified admixture. Among them, the surface modifier solution used is an aluminate coupling agent solution.

[0043] Among them, basalt sand is obtained by crushing and screening basalt, and its particle sizes are 0.2-0.4mm, 0.4-0.8mm, and 0.8-1.0mm, respectively, and are mixed in a ratio of 1:3:1.

[0044] The cement is P·Ⅱ52.5R silicate cement; the silica fume is selected from semi-densified silica fume with a bulk density of 500kg / m 3The steel fiber used is copper-plated steel fiber, with a length of 9.2 mm, a diameter of 0.2 mm, and a tensile strength of >2100 MPa. The water-reducing agent used has a water-reducing efficiency of 35%. The water-retaining agent used is a copolymer of sodium polyacrylate and polyacrylamide, with a viscosity of 200s and a sodium polyacrylate content of 88%. The defoaming agent used is a polyether-modified silicone defoaming agent.

[0045] The preparation process of ultra-high performance concrete includes the following steps: (1) According to the mass ratio of the formula, cement, silica fume, modified admixture and basalt sand are first mixed to obtain mixture A, and then mixture A is placed in a mortar mixer and stirred for 1 min; (2) Then, a certain amount of water was added to the mixture A by spraying and stirred for 4 minutes to obtain a mixture B; (3) Add a certain amount of viscosity reducer, water retaining agent, defoamer and water reducing agent to mixture B, stir and mix for 3 minutes to obtain mixture C; (4) The steel fibers are evenly sprinkled into the mixture C through a sieve and stirred for 2 minutes to obtain the ultra-high performance concrete.

[0046] Comparative Example 1 The difference between this comparative example and Example 2 is that an equal amount of unmodified admixture is added to the raw material, that is, a mixed powder of the same mass as the modified admixture of Example 1 (the mixed powder is formed by mixing mineral powder, fly ash, and ceramic polishing powder in a mass ratio of 1:3:2), and the other preparation processes and conditions are the same as those of Example 2.

[0047] Comparative Example 2 The difference between this comparative example and Example 2 is that the raw materials are added with an equal mass of single-graded basalt sand, and the single-graded basalt sand is specifically basalt sand with a particle size of (0.2-0.4 mm). Other preparation processes and conditions are consistent with Example 2.

[0048] Comparative Example 3 The difference between this comparative example and Example 2 is that the continuous graded basalt sand is added in an amount of 980 parts in the raw material. The other preparation processes and conditions are the same as those in Example 2.

[0049] Comparative Example 4 The difference between this comparative example and Example 2 is that the continuous graded basalt sand is added in an amount of 1536 parts in the raw material. The other preparation processes and conditions are the same as those in Example 2.

[0050] Comparative Example 5 The difference between this comparative example and Example 2 is that basalt sand of equal mass and different gradations is added to the raw materials, and the basalt sand is specifically: basalt sand with a particle size of (0.2-0.4 mm) and basalt sand with a particle size of (0.8-1.0 mm) are mixed in a mass ratio of 1:2. Other preparation processes and conditions are consistent with Example 2.

[0051] Performance tests of embodiments and comparative examples: The ultra-high performance concrete prepared in the above examples and comparative examples was tested for performance according to the standard: TCECS 10107-2020 "Technical Requirements for Ultra-High Performance Concrete (UHPC)", and the results are shown in Table 1: Table 1

[0052] In Table 1, "1h loss over time" and "28d compressive strength" respectively indicate the loss over time of concrete after 1 hour and the compressive strength of concrete after 28 days.

[0053] From the test results in Table 1, we can see that: With the increase of the amount of modified admixture, the expansion, 28d compressive strength and flexural strength of ultra-high performance concrete first increase and then decrease. When the amount of modified admixture is 34.1%, the expansion reaches a maximum of 710mm, which meets the requirements of TCECS10107-2020 "Technical Requirements for Ultra-High Performance Concrete (UHPC)". The specific reasons may be: Fine modified admixtures can fill the gaps between cement particles, reduce friction with fine aggregate, thereby improving the workability of concrete and increasing its expansion; but as the admixture continues to increase, excessive fine particles may cause the mixture to become too dense, thereby restricting the free flow of the concrete paste and reducing the expansion of the concrete; at this time, the 28d compressive strength also reaches a maximum of 152.5MPa, because the modified admixture can react with cement hydration products during the hydration process to generate more hydrated calcium silicate gel, which helps to improve the density and strength of the concrete; and the modified admixture helps to improve the interface transition zone between aggregate and cement paste, thereby improving the overall performance of concrete.

[0054] From the comparison between Example 2 and Comparative Example 1, the modified admixture can significantly improve the various properties of concrete; from the comparison between Example 2 and Comparative Example 2 and Comparative Example 5, the continuous graded basalt sand significantly improves the expansion and compressive strength of concrete; from the comparison between Example 2 and Comparative Example 3 and Comparative Example 4, it can be seen that increasing the amount of continuously graded basalt sand appropriately can improve its 28d compressive strength. The reason for the analysis may be: this is because basalt sand has a high density and mechanical strength, which are helpful to improve the compressive strength and wear resistance of concrete, and the continuously graded basalt sand can effectively fill the voids, reduce the porosity inside the concrete, and reduce the amount of cement slurry, thereby improving the various properties of concrete.

[0055] In addition, the present application can also overcome the potential hazards of concrete cracking caused by alkali-silica reaction in traditional concrete using quartz sand as fine aggregate, so that the concrete has good durability. The reason is that the silica content in quartz sand is generally as high as 98%. The high silica content increases the risk of alkali-silica reaction with the alkaline components in the concrete, and there is a high potential hazard of concrete expansion and eventual cracking, which has an adverse effect on the durability of the concrete. However, the present application uses basalt sand as fine aggregate, and its silica content is generally low, at about 46-52%. Therefore, the risk of alkali-silica reaction is low, and the addition of basalt sand can control the material conditions for the formation of gypsum and calcium aluminate, and inhibit the formation and quantity of expansive hydration products; on the other hand, its "dilution effect", "microcrystalline nucleus effect" and "filling effect" synergistically can improve the internal porosity and pore size distribution of concrete, increase the early density of concrete, prevent the invasion of corrosive medium sulfate ions, and fundamentally improve the durability of concrete.

[0056] The reason why the ultra-high performance concrete provided by the present application has good asphalt adhesion is that in the traditional concrete using quartz sand as fine aggregate, the surface texture of the fine aggregate quartz sand particles is smooth, and the asphalt is evenly distributed and uniformly thick when coated on its surface, and the adsorption effect is weak. However, the present application uses basalt sand as fine aggregate, and its surface texture is rough and porous, which significantly enhances the adsorption effect of asphalt. In addition, the basalt sand particles are staggered in the asphalt, and the accumulation and friction between the particles make it form a more tightly combined whole. Therefore, the basalt sand has good adhesion to asphalt. The concrete using basalt sand as fine aggregate provided by the present application has good asphalt adhesion.

[0057] In summary, the ultra-high performance concrete provided in the embodiment of the present application can give full play to the advantages of high strength and high toughness of ultra-high performance concrete while having good working performance, and can also have road performance such as good wear resistance, light weight, good adhesion to asphalt, and it also has the advantage of good durability. In addition, the ultra-high performance concrete solution uses modified admixtures to replace part of the cement, reducing the overall material cost.

[0058] In summary, the present application scheme has at least the following design concepts and beneficial effects: (1) By modifying the admixture, on the one hand, its volcanic ash activity can be further improved, so that it can participate in the hydration reaction well and generate more hydration products to improve its strength; on the other hand, the modification makes it easier to disperse in the concrete and prevents agglomeration.

[0059] (2) This application uses modified admixtures to replace part of the cement, reducing the overall material cost.

[0060] (3) Basalt sand is taken from basalt, also known as pumice. It has many pores and a hard texture. It can reduce the weight of concrete. It is not only strong and durable, but also has the characteristics of sound insulation and heat insulation. It is a good aggregate for high-rise building concrete. It also has the advantages of strong compressive resistance, low crushing value, strong corrosion resistance, wear resistance, low water draft, strong corrosion resistance, and good asphalt adhesion.

[0061] The basalt sand used in this application is used in ultra-high performance concrete for the first time. Because of its advantages such as strong compressive resistance, low crushing value, strong corrosion resistance, wear resistance, low water draft, strong corrosion resistance and good asphalt adhesion, it is compatible with ultra-high performance concrete, meets the requirements of road materials, and greatly improves the performance of concrete.

[0062] (4) The preparation process of the ultra-high performance concrete of the present application is simple and easy to operate, which is conducive to saving a lot of manpower costs.

[0063] In summary, the ultra-high performance concrete prepared in the present application greatly improves its compressive strength by continuously grading and closely stacking the fine aggregate basalt sand material to replace the common fine aggregate quartz sand, and effectively reduces the cost of ultra-high performance concrete by replacing part of the cement with modified admixtures.

[0064] It should be noted that: In this article, “~” is used to indicate a numerical range, and the range indicated by this expression includes two endpoint values.

[0065] In summary, the specific parameters or some commonly used reagents or raw materials in the above embodiments are specific embodiments or preferred embodiments of the present application, but are not intended to limit the present application. Those skilled in the art may make adaptive adjustments within the scope of the present application.

[0066] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

Claims

1. An ultra-high performance concrete prepared with continuously graded basalt sand, characterized in that: Including the following raw material components: cement, silica fume, modified admixture, basalt sand, steel fiber, viscosity reducer, water retaining agent, defoamer, water reducing agent, water; The basalt sand comprises a first type of basalt sand, a second type of basalt sand and a third type of basalt sand, the particle sizes of the first type of basalt sand, the second type of basalt sand and the third type of basalt sand are (0.2-0.4) mm, (0.4-0.8) mm and (0.8-1.0) mm respectively, and the mass ratio of the first type of basalt sand, the second type of basalt sand and the third type of basalt sand is (1-4): (6-8): (2-4); The modified admixture is obtained by subjecting a mixed material to surface modification treatment with a surface modifier solution; wherein the mixed material is obtained by mixing mineral powder, fly ash, ceramic polishing powder and diethanol monoisopropanolamine and subjecting the mixed material to ball milling treatment.

2. The ultra-high performance concrete prepared with continuously graded basalt sand according to claim 1, characterized in that: The preparation process of the modified admixture is as follows: The ore powder, fly ash and ceramic polishing powder are mixed to form a mixed powder, and then diethanol monoisopropanolamine is added to perform ball milling for 40 to 60 minutes to obtain a mixed material; then a surface modifier solution is added to perform surface modification treatment, and the mixture is stirred at 40 to 80° C. for (5 to 10) minutes, filtered, and finally dried to obtain the modified admixture; Among them, the mass ratio of the mineral powder, the fly ash and the ceramic polishing powder is (1-3): (3-5): (2-6); the amount of diethanol monoisopropanolamine is 0.01% to 0.03% of the mass of the mixed powder; and the amount of the surface modifier solution is 8 to 12 times the mass of the mixture.

3. The ultra-high performance concrete prepared with continuously graded basalt sand according to claim 1, characterized in that: The basalt sand is obtained by crushing and screening basalt; The basalt sand consists of first-type basalt sand, second-type basalt sand and third-type basalt sand.

4. The ultra-high performance concrete prepared with continuously graded basalt sand according to claim 1, characterized in that: By mass, it includes the following raw material components: 480-800 parts of cement, 100-200 parts of silica fume, 330-650 parts of modified admixtures, 1000-1500 parts of basalt sand, 40-160 parts of steel fiber, 2-10 parts of viscosity reducer, 5-10 parts of water retaining agent, 2-6 parts of defoaming agent, 1-3 parts of water reducing agent, and 192-250 parts of water.

5. The ultra-high performance concrete prepared with continuously graded basalt sand according to claim 4, characterized in that: By mass, it includes the following raw material components: 600-700 parts of Portland cement, 120-180 parts of silica fume, 400-600 parts of modified admixtures, 1200-1400 parts of basalt sand, 60-120 parts of steel fiber, 4-8 parts of viscosity reducer, 6-8 parts of water retaining agent, 2-4 parts of defoaming agent, 1-2 parts of water reducing agent, and 206-240 parts of water.

6. The ultra-high performance concrete prepared with continuously graded basalt sand according to claim 1, characterized in that: The cement is one or a combination of P·Ⅰ52.5R silicate cement, P·Ⅱ52.5R silicate cement, P·O 52.5R ordinary silicate cement; The silica fume is one of white silica fume, semi-densified silica fume, and fully-densified silica fume, or a combination of two thereof, and its bulk density is 500 kg / m 3 .

7. The ultra-high performance concrete prepared with continuously graded basalt sand according to claim 1, characterized in that: The steel fiber is a copper-plated steel fiber with a length of 9 to 17 mm, a diameter of 0.1 to 0.3 mm, and a tensile strength of more than 2100 MPa.

8. The ultra-high performance concrete prepared with continuously graded basalt sand according to claim 1, characterized in that: The water reducing agent has a water reducing rate of 30 to 36%; The water retaining agent is a copolymer cross-linked product of sodium polyacrylate and polyacrylamide, with a viscosity of 200s and a sodium polyacrylate content of 88%.

9. A method for preparing ultra-high performance concrete using continuously graded basalt sand as claimed in any one of claims 1 to 8, characterized in that: The method comprises the following preparation steps: Firstly, cement, silica fume, modified admixture and basalt sand are mixed according to mass ratio to obtain mixture A, and mixture A is stirred and mixed uniformly; A certain amount of water was added to the mixture A by spraying, and the mixture was stirred to obtain a mixture B; Add a certain amount of viscosity reducer, water retaining agent, defoamer and water reducing agent to mixture B, stir and mix, and obtain mixture C; The steel fibers are evenly sprinkled into the mixture C through a sieve and stirred evenly to obtain the ultra-high performance concrete.

10. The method for preparing ultra-high performance concrete using continuously graded basalt sand according to claim 9, characterized in that: Place mixture A in a mortar mixer and stir for 1 to 3 minutes; Add a certain amount of water to mixture A by spraying, and stir for 3 to 6 minutes to obtain mixture B; Add a certain amount of viscosity reducer, water retaining agent, defoamer and water reducing agent to mixture B, and stir for 2 to 4 minutes to obtain mixture C; The steel fibers are evenly sprinkled into the mixture C through a sieve, and after stirring for 2 to 3 minutes, the ultra-high performance concrete is obtained.

Citation Information

Cited By

  • Modified ultrafine fly ash, UHPC, preparation method and application

    CN121717568A